Hyphaema in phacolytic glaucoma, a case report. - Suhardjo Suhardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Phacolytic glaucoma is a secondary glaucoma which occurs in open angle hypermature cataract and caused by trabecular obstruction. This abstruction occurs due to the leaked of lens protein through an intact capsule. Hyphaema in phacolytic glaucoma is an unusual case.Objective : To evaluate the result of conservative therapy and extra capsular cataract extraction on phacolytic glaucoma associated with hyphaema.Methods :A case of hyphaema in phacolytic glaucoma has been reported in a 62 year old man. Symptoms of decreased visual acuity, pain, headache were found in this case. Ophthalmology examination found right visual acuity 1/